Appearance
โThe difference of two numbers is a certain value. On dividing the larger number by the smaller, we get 6 as quotient and 10 as remainder. The larger number is 1636. What is the difference between the two numbers?
๐กFirst, I recognize that the larger number is given as 1636. When this number is divided by the smaller number, the quotient is 6 and the remainder is 10. This relationship can be expressed using the equation:1636 = 6S + 10To find the smaller number (S), I subtract the remainder from the larger number:1636 - 10 = 1626Next, I divide this result by the quotient to determine the value of the smaller number:1626 รท 6 = 271Now that I have both numbers, the larger number is 1636 and the smaller number is 271. To find the difference between the two numbers, I subtract the smaller number from the larger number:1636 - 271 = 1365Therefore, the difference between the two numbers is 1365.
โIf xgeq 0, then sqrt{xsqrt{xsqrt{x}}}=textbf{(A) } xsqrt{x}qquad textbf{(B) } xsqrt[4]{x}qquad textbf{(C) } sqrt[8]{x}qquad textbf{(D) } sqrt[8]{x^3}qquad textbf{(E) } sqrt[8]{x^7}
๐กOkay, so I have this problem here: If ( x geq 0 ), then ( sqrt{xsqrt{xsqrt{x}}} ) equals which of the given options? The options are:A) ( xsqrt{x} )B) ( xsqrt[4]{x} )C) ( sqrt[8]{x} )D) ( sqrt[8]{x^3} )E) ( sqrt[8]{x^7} )Alright, let me try to figure this out step by step. I remember that when dealing with nested square roots, it's helpful to express them using exponents because exponents are easier to manipulate. So, I'll start by rewriting each square root as a power of ( frac{1}{2} ).First, let's look at the innermost square root: ( sqrt{x} ). That can be written as ( x^{1/2} ).Now, moving one level out, we have ( sqrt{xsqrt{x}} ). Substituting the innermost square root, this becomes ( sqrt{x cdot x^{1/2}} ). When multiplying variables with exponents, we add the exponents. So, ( x ) is ( x^{1} ) and ( x^{1/2} ) is ( x^{1/2} ). Adding the exponents: ( 1 + 1/2 = 3/2 ). Therefore, ( x cdot x^{1/2} = x^{3/2} ).So now, ( sqrt{xsqrt{x}} = sqrt{x^{3/2}} ). Again, a square root is the same as raising to the power of ( 1/2 ), so this becomes ( (x^{3/2})^{1/2} ). When raising a power to another power, we multiply the exponents: ( 3/2 times 1/2 = 3/4 ). So, ( sqrt{xsqrt{x}} = x^{3/4} ).Moving out to the outermost square root, we have ( sqrt{xsqrt{xsqrt{x}}} ). We already found that ( sqrt{xsqrt{x}} = x^{3/4} ), so substituting that in, we get ( sqrt{x cdot x^{3/4}} ).Again, when multiplying variables with exponents, we add the exponents. Here, ( x ) is ( x^{1} ) and ( x^{3/4} ) is ( x^{3/4} ). Adding the exponents: ( 1 + 3/4 = 7/4 ). So, ( x cdot x^{3/4} = x^{7/4} ).Therefore, ( sqrt{xsqrt{xsqrt{x}}} = sqrt{x^{7/4}} ). Converting the square root to an exponent, this becomes ( (x^{7/4})^{1/2} ). Multiplying the exponents: ( 7/4 times 1/2 = 7/8 ). So, ( sqrt{xsqrt{xsqrt{x}}} = x^{7/8} ).Now, looking at the answer choices, I need to express ( x^{7/8} ) in a form that matches one of the options. Remember that ( x^{7/8} ) can be written as the 8th root of ( x^7 ), which is ( sqrt[8]{x^7} ). That corresponds to option E.Let me double-check my steps to make sure I didn't make any mistakes. Starting from the inside:1. ( sqrt{x} = x^{1/2} )2. ( sqrt{x cdot x^{1/2}} = sqrt{x^{3/2}} = x^{3/4} )3. ( sqrt{x cdot x^{3/4}} = sqrt{x^{7/4}} = x^{7/8} )Yes, that seems correct. And ( x^{7/8} ) is indeed ( sqrt[8]{x^7} ), so option E is the right answer.I think I got it!**Final Answer**boxed{E}
โAmong the following points, the point that is not on the graph of the inverse proportion function y=frac{6}{x} is:A: (-2,-3)B: (-3,-2)C: (1,5)D: (4,1.5)
๐กFirst, I need to determine which of the given points does not lie on the graph of the inverse proportion function ( y = frac{6}{x} ).I recall that for an inverse proportion function ( y = frac{k}{x} ), the product of ( x ) and ( y ) should always equal the constant ( k ). In this case, ( k = 6 ).To verify each point, I will calculate the product ( x times y ) and check if it equals 6.**For point A: ((-2, -3))**[x times y = (-2) times (-3) = 6]This satisfies the equation ( x times y = 6 ).**For point B: ((-3, -2))**[x times y = (-3) times (-2) = 6]This also satisfies the equation ( x times y = 6 ).**For point C: ((1, 5))**[x times y = 1 times 5 = 5]This does not equal 6, so point C does not satisfy the equation.**For point D: ((4, 1.5))**[x times y = 4 times 1.5 = 6]This satisfies the equation ( x times y = 6 ).After checking all points, only point C does not satisfy the equation ( x times y = 6 ). Therefore, point C is not on the graph of the function ( y = frac{6}{x} ).
โTo obtain the graph of the function y=4cos 2x, all you need to do is move each point ( ) on the graph of the function y=4cos (2x+ frac {ฯ}{4}):A: horizontally to the left by frac {ฯ}{4} unitsB: horizontally to the right by frac {ฯ}{4} unitsC: horizontally to the left by frac {ฯ}{8} unitsD: horizontally to the right by frac {ฯ}{8} units
๐กOkay, so I have this problem here about graph transformations of cosine functions. It says that to get the graph of y = 4 cos(2x), I need to move each point on the graph of y = 4 cos(2x + ฯ/4) either left or right by some units. The options are A: left by ฯ/4, B: right by ฯ/4, C: left by ฯ/8, and D: right by ฯ/8. Hmm, I need to figure out which one is correct.First, I remember that when dealing with function transformations, especially with trigonometric functions like cosine, the general form is y = A cos(Bx + C) + D. In this case, both functions have the same amplitude, which is 4, so that part doesn't change. The question is about the horizontal shift, which is related to the phase shift.The phase shift formula for a cosine function is given by -C/B. So, if I have y = 4 cos(2x + ฯ/4), I can rewrite this as y = 4 cos[2(x + ฯ/8)]. That's because factoring out the 2 from inside the cosine function gives me 2(x + ฯ/8). So, the phase shift here is -ฯ/8, which means the graph is shifted ฯ/8 units to the left.Wait, but the question is asking how to get from y = 4 cos(2x + ฯ/4) to y = 4 cos(2x). So, if the original function is shifted ฯ/8 to the left, then to reverse that shift and get back to the original cosine function without the phase shift, I need to move it ฯ/8 to the right. That makes sense because shifting left and then right by the same amount cancels out the shift.Let me double-check that. If I have y = 4 cos(2x + ฯ/4), and I want to get to y = 4 cos(2x), I can think of it as removing the phase shift. So, if the original function was shifted left by ฯ/8, then to get back, I shift it right by ฯ/8. That should align the two graphs correctly.Another way to think about it is by considering the transformation steps. Starting with y = 4 cos(2x + ฯ/4), I can factor out the 2 from the argument of the cosine to make it easier to see the shift. So, 2x + ฯ/4 becomes 2(x + ฯ/8). This shows that the graph is shifted ฯ/8 units to the left. Therefore, to reverse this shift, I need to shift it ฯ/8 units to the right.I can also test this by plugging in a specific value. Let's say x = 0. For the original function, y = 4 cos(ฯ/4) = 4*(โ2/2) = 2โ2. For the target function y = 4 cos(0) = 4. So, if I shift the point (0, 2โ2) to the right by ฯ/8, the new x-coordinate becomes ฯ/8, and the y-value should be 4 cos(2*(ฯ/8)) = 4 cos(ฯ/4) = 2โ2. Wait, that doesn't seem to help much because the y-values are different. Maybe I need a different approach.Alternatively, let's consider the general transformation. If I have y = 4 cos(2x + ฯ/4), and I want to write it as y = 4 cos[2(x - h)], where h is the horizontal shift. Expanding this, it becomes y = 4 cos(2x - 2h). Comparing this to the original function, 2x + ฯ/4, we can set -2h = ฯ/4, which gives h = -ฯ/8. A negative h means a shift to the left by ฯ/8. Therefore, to get back to y = 4 cos(2x), I need to shift it to the right by ฯ/8.That seems consistent with what I thought earlier. So, the correct answer should be D: horizontally to the right by ฯ/8 units.Just to make sure, let's visualize the graphs. The function y = 4 cos(2x + ฯ/4) is a cosine wave with amplitude 4, period ฯ (since the period is 2ฯ/B, and B is 2 here), and shifted ฯ/8 to the left. The function y = 4 cos(2x) has the same amplitude and period but is not shifted. So, to go from the shifted graph to the unshifted one, I need to move everything back to the right by ฯ/8.Yeah, I think that's solid. So, the answer is D.
โWhat is the area of the region enclosed by the graph of the equation x^2 + 2x + 3y + 50 = 35 + 15y - y^2 that lies above the line y = -x + 5?
๐กOkay, so I have this problem here: I need to find the area of the region enclosed by the graph of the equation (x^2 + 2x + 3y + 50 = 35 + 15y - y^2) that lies above the line (y = -x + 5). Hmm, that sounds a bit complicated, but let me try to break it down step by step.First, I think I need to figure out what kind of graph this equation represents. It has both (x^2) and (y^2) terms, so maybe it's a circle? Let me try rearranging the equation to see if I can get it into the standard form of a circle, which is ((x - h)^2 + (y - k)^2 = r^2), where ((h, k)) is the center and (r) is the radius.Starting with the given equation:[x^2 + 2x + 3y + 50 = 35 + 15y - y^2]I should move all the terms to one side to see if I can simplify it. Let me subtract (35 + 15y - y^2) from both sides:[x^2 + 2x + 3y + 50 - 35 - 15y + y^2 = 0]Simplifying the constants and like terms:- (50 - 35 = 15)- (3y - 15y = -12y)So the equation becomes:[x^2 + 2x + y^2 - 12y + 15 = 0]Hmm, that looks closer to the standard circle equation. Now, I need to complete the square for both the (x) terms and the (y) terms.Starting with the (x) terms: (x^2 + 2x). To complete the square, I take half of the coefficient of (x), which is (2/2 = 1), and square it, getting (1^2 = 1). So I add and subtract 1:[(x^2 + 2x + 1 - 1)]Similarly, for the (y) terms: (y^2 - 12y). Half of (-12) is (-6), and squaring that gives (36). So I add and subtract 36:[(y^2 - 12y + 36 - 36)]Putting it all back into the equation:[(x^2 + 2x + 1) - 1 + (y^2 - 12y + 36) - 36 + 15 = 0]Simplifying:[(x + 1)^2 - 1 + (y - 6)^2 - 36 + 15 = 0]Combine the constants:[-1 - 36 + 15 = -22]So the equation becomes:[(x + 1)^2 + (y - 6)^2 - 22 = 0][(x + 1)^2 + (y - 6)^2 = 22]Alright, so now it's clear that this is a circle with center at ((-1, 6)) and radius (sqrt{22}). Good, that wasn't too bad.Next, I need to find the area of the region of this circle that lies above the line (y = -x + 5). So, I guess I need to figure out how this line interacts with the circle. Does it intersect the circle? If so, where? And then, based on that, determine the area above the line.First, let me visualize this. The circle is centered at ((-1, 6)) with a radius of approximately 4.69 (since (sqrt{22} approx 4.69)). The line is (y = -x + 5), which is a straight line with a slope of (-1) and y-intercept at 5. So it's a diagonal line going from the upper left to the lower right.I need to find if this line intersects the circle. If it does, the area above the line will be a segment of the circle. To find the area of that segment, I might need to calculate the angle subtended by the chord formed by the intersection points and then use the formula for the area of a circular segment.But before that, let me find the points where the line intersects the circle. To do this, I can substitute (y = -x + 5) into the circle equation and solve for (x).Substituting (y = -x + 5) into ((x + 1)^2 + (y - 6)^2 = 22):[(x + 1)^2 + (-x + 5 - 6)^2 = 22]Simplify the (y) term:[(x + 1)^2 + (-x - 1)^2 = 22]Now, expand both squares:First, ((x + 1)^2 = x^2 + 2x + 1)Second, ((-x - 1)^2 = x^2 + 2x + 1)So, adding them together:[x^2 + 2x + 1 + x^2 + 2x + 1 = 22]Combine like terms:[2x^2 + 4x + 2 = 22]Subtract 22 from both sides:[2x^2 + 4x + 2 - 22 = 0][2x^2 + 4x - 20 = 0]Divide the entire equation by 2 to simplify:[x^2 + 2x - 10 = 0]Now, solve for (x) using the quadratic formula:[x = frac{-b pm sqrt{b^2 - 4ac}}{2a}]Here, (a = 1), (b = 2), (c = -10):[x = frac{-2 pm sqrt{(2)^2 - 4(1)(-10)}}{2(1)}][x = frac{-2 pm sqrt{4 + 40}}{2}][x = frac{-2 pm sqrt{44}}{2}]Simplify (sqrt{44}) as (2sqrt{11}):[x = frac{-2 pm 2sqrt{11}}{2}]Factor out 2 in numerator:[x = frac{2(-1 pm sqrt{11})}{2}]Cancel out the 2:[x = -1 pm sqrt{11}]So, the x-coordinates of the intersection points are (x = -1 + sqrt{11}) and (x = -1 - sqrt{11}). Now, let's find the corresponding y-coordinates using the line equation (y = -x + 5).For (x = -1 + sqrt{11}):[y = -(-1 + sqrt{11}) + 5 = 1 - sqrt{11} + 5 = 6 - sqrt{11}]For (x = -1 - sqrt{11}):[y = -(-1 - sqrt{11}) + 5 = 1 + sqrt{11} + 5 = 6 + sqrt{11}]So, the points of intersection are ((-1 + sqrt{11}, 6 - sqrt{11})) and ((-1 - sqrt{11}, 6 + sqrt{11})).Now, I need to figure out the area of the circle above the line (y = -x + 5). Since the line intersects the circle at two points, the area above the line is a circular segment. To find the area of this segment, I can use the formula:[ text{Area of segment} = frac{1}{2} r^2 (theta - sin theta) ]where (theta) is the central angle in radians subtended by the chord connecting the two intersection points.To find (theta), I can use the distance from the center of the circle to the line. If I can find this distance, I can relate it to the radius to find the angle.The formula for the distance (d) from a point ((h, k)) to the line (Ax + By + C = 0) is:[ d = frac{|Ah + Bk + C|}{sqrt{A^2 + B^2}} ]First, let me write the line equation in standard form. The given line is (y = -x + 5). Let's rearrange it:[ x + y - 5 = 0 ]So, (A = 1), (B = 1), and (C = -5).The center of the circle is ((-1, 6)). Plugging into the distance formula:[ d = frac{|1(-1) + 1(6) - 5|}{sqrt{1^2 + 1^2}} ][ d = frac{|-1 + 6 - 5|}{sqrt{2}} ][ d = frac{|0|}{sqrt{2}} ][ d = 0 ]Wait, that can't be right. If the distance is zero, that would mean the center lies on the line. But looking back, let me double-check the calculation.The line is (x + y - 5 = 0). Plugging in the center ((-1, 6)):[ (-1) + 6 - 5 = 0 ][ 0 = 0 ]Oh! So the center is actually on the line. That means the line passes through the center of the circle. Therefore, the line is a diameter of the circle, and it divides the circle into two equal halves.But wait, the problem asks for the area above the line (y = -x + 5). If the line passes through the center, then the area above the line is exactly half of the circle's area.So, the area of the circle is:[ text{Area} = pi r^2 = pi (sqrt{22})^2 = 22pi ]Therefore, the area above the line is half of that:[ text{Area above the line} = frac{22pi}{2} = 11pi ]But hold on, let me make sure I didn't make a mistake earlier. I thought the distance was zero, implying the center is on the line, which would mean the line is a diameter. But let me verify the intersection points.We found the intersection points at ((-1 + sqrt{11}, 6 - sqrt{11})) and ((-1 - sqrt{11}, 6 + sqrt{11})). Let me check if these points are symmetric with respect to the center ((-1, 6)).For the first point: ((-1 + sqrt{11}, 6 - sqrt{11})). The distance from the center in the x-direction is (sqrt{11}), and in the y-direction is (-sqrt{11}).For the second point: ((-1 - sqrt{11}, 6 + sqrt{11})). The distance from the center in the x-direction is (-sqrt{11}), and in the y-direction is (sqrt{11}).So, these points are indeed symmetric with respect to the center, which is consistent with the line passing through the center. Therefore, the line is a diameter, and the area above the line is exactly half the circle's area.Therefore, the area is (11pi).But wait, let me think again. The problem says "the region enclosed by the graph... that lies above the line." If the line is a diameter, then the area above the line is a semicircle, which is half the area of the circle. So yes, that should be correct.I think I was overcomplicating it earlier by trying to find the angle and all that. Once I realized the center is on the line, it simplifies everything.So, final answer: The area is (11pi).**Final Answer**The area of the region is boxed{11pi}.
โMixture A is 20 percent alcohol, and mixture B is 50 percent alcohol. If the two are poured together to create a 15-gallon mixture that contains some percent alcohol, and there are approximately 10 gallons of mixture A in the mixture. What is the percentage of alcohol in the final mixture?
๐กFirst, determine the amount of mixture B by subtracting the amount of mixture A from the total volume: (15 - 10 = 5) gallons.Next, calculate the amount of alcohol from each mixture:- Alcohol from mixture A: (0.20 times 10 = 2) gallons.- Alcohol from mixture B: (0.50 times 5 = 2.5) gallons.Add the amounts of alcohol to find the total alcohol in the final mixture: (2 + 2.5 = 4.5) gallons.Finally, calculate the percentage of alcohol in the final mixture by dividing the total alcohol by the total volume and multiplying by 100: (frac{4.5}{15} times 100 = 30%).